The Effect of Product Information on The Consumers Preference of Local Various Chocolate Bar - Malau, Krisna Margaretta; Ataribaba, Yuliana; Armetha, Vallerina (Green Engineering Society, 2024)
Chocolate producers need to know and understand the tastes of the Indonesian people specifically when making decisions to purchase chocolate bars. Research on the characteristics of the types of chocolate bars that consumers like is still needed to be able to reach a wider target market. The hedonic rating test requires panelists to measure the level of liking of the sample from most liked to least liked. The majority of teenagers and adult consumers in Indonesia are involved as panelists according to demographic research on chocolate consumers. The samples tested were six brands of chocolate bars circulating on the Manokwari city market. The panelists involved were 160 consumers (67 men; 93 women, aged 13–24 years). The sensory test method used was the hedonic rating test which was presented in two variants of serving method: (1) blind test (without additional information) (2) informed test (product variants and brand information accompanied by the product in intact packaging). To identify the influence of the variant of chocolate in the sample, the Friedman test and Duncan’s advanced test were used at a significance level of 5%. To identify the effect of information, intervention using non-parametric analysis using averages with the Mann-Whitney U test was used. The results of the chocolate preference level test showed that there was a significant difference in preference of variants chocolate (at a significance level of 0.05), whereas in the information intervention test of brand and variant of chocolate, there were samples that had significant differences in preferences.